Correlation between damage distribution and soil characteristics deduced from ambient vibrations in the old town of Lefkada (W. Greece) - Kassaras, I.; Kalantoni, D.; V. Kouskouna; Pomonis, A.; Michalaki, K.; P. Stoumpos; S. Mourloukos; S. Birmpilopoulos; Makropoulos, K. (Second European Conference on Earthquake Engineering and Seismology (2ECEES), 2014)
This work is part of a multi-parametric research towards representation of damage scenarios in the Lefkada old town. The study area lies in the most seismically active zone of the Greek territory. Most of its buildings were built with local practices and have been designated by the European Council Cultural Heritage Unit as representative earthquake resistant constructions. The August 14th, 2003 (Mw=6.2) local earthquake produced several damage in the old town of Lefkada, with an inhomogeneous spatial distribution. In this paper we investigate the correlation of the observed damage pattern with soil characteristics using data collected during an ambient noise survey conducted in 2007. Those were analyzed following Nakamura's HVSR methodology and soil response was approximated by the dominant frequencies and quasi-amplification factors of the resulted HVSR curves. The latter were further inverted using a Monte-Carlo approach and best-fitting site specific geotechnical models were determined. The obtained results are reasonably consistent with borehole test data and show a remarkably good correlation with the 2003 damage distribution.